Out of 2 n + 1 tickets numbered consecutively, three are drawn (without replacement) at random. The chance that the numbers on them are in an arithmetic progression is?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Can i think in this way that I need two numbers between 1 & n+1 (both included), for forming an AP, so, I have n^2 chances of picking in that way... Automatically, my 3rd number will be selected to form an AP...
In any 3 term AP, the first and third term must have the same parity (odd or even) If They do, there will be an integral second term which is the mean of the first and third. So, number of desired outcomes is equal to the number of ways of picking 2 numbers from all odd terms + number of ways of picking two numbers out of all even terms.
This would be Nc2 + N+1c2 which equals n^2
Lol,put n=1 .!!!! . . . . . . . . . . .
This solution has been marked wrong because you had only that it's true for n = 1 .
To avoid confusion the problem should state that the numbers are picked without replacement.
Hey! The fastest method to right ans is the best method .
For n = 1 we have probability 1 of obtaining numbers from an arithmetic progression. Out of the four choices only 4 n 2 − 1 3 n is consistent with the fact.
Problem Loading...
Note Loading...
Set Loading...
Let the 3 numbers chosen from the 2 n + 1 consecutive integers be arranged in ascending order. Then if they are in AP, there will be a minimum difference (magnitude) of d = 1 between successive terms, and a maximum difference (magnitude) of d = n , (since 2 n + 1 is always odd).
There will be ( 2 n + 1 ) − 2 AP sequences with d = 1 , ( 2 n + 1 ) − 4 AP sequences with d = 2 , and in general ( 2 n + 1 ) − 2 m AP sequences with d = m . Thus the number of AP's that can be obtained is
k = 1 ∑ n ( 2 k − 1 ) = 2 k = 1 ∑ n k − k = 1 ∑ n 1 = n ( n + 1 ) − n = n 2 .
Now there are ( 3 2 n + 1 ) = 6 ( 2 n + 1 ) ( 2 n ) ( 2 n − 1 ) = 3 n ( 4 n 2 − 1 ) possible draws without restrictions, so the desired probability is
3 n ( 4 n 2 − 1 ) n 2 = 4 n 2 − 1 3 n .